Applied econometric time series - Enders, Walter, 1948- (John Wiley and Sons, Inc., 2015)
Applied Econometric Time Series, 4th Edition demonstrates modern techniques for developing models capable of forecasting, interpreting, and testing hypotheses concerning economic data. In this text, Dr. Walter Enders commits to using a "learn-by-doing" approach to help readers master time-series analysis efficiently and effectively.